Copper-chromite glass fiber catalyst and its performance in the test reaction of deep oxidation of toluene in air; Reaction Kinetics, Mechanisms and Catalysis; Vol. 120, iss. 1 - Zazhigalov S. Sergey; Elyshev A. Andrey; Lopatin S. Sergey; Larina T. Tatyana; Cherepanova S. Svetlana; Mikenin P. Pavel; Pisarev D. Danil; Baranov D. Dmitry; Zagoruiko A. N. Andrey Nikolaevich (2017, 2017)
Title screen